(untitled) (Annals of Medical Research, 2021)
Aim: To determine the gynecological pathologies accompanying perimenopausal (PEM) and postmenopausal (PM) adenomyosis and to determine which of these pathologies may contribute to the etiology of adenomyosis. Materials and Methods: We retrospectively reviewed pathology report archives from between 2008 and 2018 and identified surgical hysterectomy specimens that were histopathologically diagnosed as cases of adenomyosis and the accompanying gynecological pathologies. Data regarding medical history were obtained from patient files. The patients were divided into two groups, PEM and PM, and they were compared. Results: There were a total of 212 patients (154 PEM and 58 PM) diagnosed with adenomyosis by histopathological examination of hysterectomy specimens. The most common complaints in the PEM patients were abnormal uterine bleeding and pelvic pain, and adenomyosis was frequently diagnosed incidentally in the PM women who underwent hysterectomy due to prolapse. The most common concomitant pathology among all patients was uterine leiomyomas, which affected 102 patients (48.1%), 80 of whom were in the PEM group and 22 in the PM group. The second most common accompanying pathology was endometrial polyps (22.2%, n =47), which was more common among the PM patients (PEM 16.9%, n = 26; PM 36.2%, n = 21). Endometriosis was more prominent in the PEM patients (12.3% n = 19), and 11.6% of the PEM patients had endometrial hyperplasia. Conclusion: Uterine leiomyoma was the most common gynecological pathology accompanying adenomyosis in both groups, and endometriosis and endometrial hyperplasia were significantly more common in the PEM group compared to the PM group. In line with our results, we think that common etiopathogenic factors may play a role in the pathogenesis of adenomyosis and the concomitant pathologies, and we have discussed our findings here in the light of the literature.